PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL DIBIDANG PATEN - Mastur Mastur (Fakultas Hukum Universitas Wahid Hasyim, 2012)
Intellectual Property Rights are rights derived from the work, initiative and creativity in the form of a real man. Intellectual Property rights consist of privately owned property and Industry. Patents are part of Intellectual Property Rights in Industry. Patents are granted the right of the government and is exclusive. Exclusive rights of patent holders is the production of a patented item, usage and sales of goods and deeds relating to the import and sale of such goods store. Legal protection of intellectual property rights in the patent field ketetentuan regulated in Law Number 14 of 2001. In chapter 8, paragraph (1) time protection for 20 years from the date of receipt and can not be extended. And Article 9 set period of patent protection for simple for 10 (ten) years and can not be extended. Protection of intellectual property rights is no guarantee to the public to respect the right of initiative and the reaction and to provide protection will upload their work. The higher appreciation of the intellectual property rights of a nation then the future will be better .Keywords: Intellectual Property Rights, Patent Protection